Invisible coating material for aviation aircraft
The stealth coating material for aircraft, designed with a three-layer functional composite structure, solves the problems of multispectral stealth, lightweighting and long life of existing coating materials, and realizes adaptive adjustment and self-repair functions, thereby improving stealth effect and reliability.
Patent Information
- Application Number
- CN202511683249.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2026-01-23
AI Technical Summary
Existing stealth coating materials have limited functionality, static characteristics, are difficult to maintain, and have poor environmental adaptability, making it difficult to meet the requirements for multispectral stealth, lightweighting, and long lifespan.
It adopts a three-layer functional composite structure design, including an intelligent sensing layer, a tunable metamaterial layer and a multispectral stealth layer, and combines nanotechnology and intelligent responsive materials to achieve adaptive adjustment and self-repair functions.
It achieves radar wave absorption in the ultra-wide frequency band of 0.1-40GHz, reduces infrared radiation characteristics by 80%, dynamically adjusts visible light reflectivity, reduces surface density by 60%, extends service life to 10 years, and reduces maintenance costs by 70%.
Smart Images

Figure CN121379324A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of aerospace materials, and particularly relates to an aircraft stealth coating material. BACKGROUND
[0002] With the rapid development of modern military technology, the stealth performance of aircraft has become one of the key factors determining the advantage of air combat. Stealth technology can significantly improve the survivability and penetration success rate of aircraft by reducing the detectability of aircraft under radar, infrared, visible light and other detection means. Among various stealth technologies, stealth coating materials, as a relatively simple and cost-effective solution, have been widely used on military aircraft. Such materials not only need to have excellent electromagnetic wave absorption performance, but also need to meet the strict requirements of the aviation field on material weight, durability, maintainability and other aspects. Therefore, the development of new high-performance stealth coating materials has always been the research focus and technical difficulty in the field of aviation materials.
[0003] The existing aircraft stealth coating technology mainly uses radar wave absorbing materials to realize the absorption and attenuation of electromagnetic waves. Traditional wave absorbing material systems include ferrite-based wave absorbing coatings, carbon-based composite material coatings and conductive polymer coatings. Ferrite-based coatings absorb electromagnetic waves through magnetic loss mechanism, usually using barium ferrite, manganese zinc ferrite and other materials. Such coatings have good wave absorption effect in the frequency band of 2-18GHz, but have the problems of large density and thick coating, with a typical surface density of 4-6kg / m². Carbon-based composite material coatings mainly use the dielectric loss characteristics of carbon materials such as carbon black, carbon fiber and graphene. Although the weight is relatively light, the wave absorption frequency band is narrow, and multiple layer composite structures are usually needed to achieve wide frequency absorption. In recent years, the development of metamaterial technology has provided a new idea for stealth coating. By designing periodic artificial electromagnetic structures, the precise regulation of electromagnetic wave propagation characteristics can be realized, but the existing metamaterial stealth coating is mostly a static structure and cannot adaptively adjust according to the changes of threat signals.
[0004] However, the existing stealth coating technology has many technical bottlenecks which seriously restrict its application effect. First of all, the problem of single function, most of the existing coatings can only achieve single wave band stealth effect, it is difficult to deal with radar, infrared, visible light and other detection means, and simple multi-layer superposition will lead to thick and heavy coating, affecting the aerodynamic performance and load capacity of the aircraft. Secondly, the static characteristics of the stealth performance, the electromagnetic parameters of the traditional coating are fixed and cannot be optimized according to the detection signal of different frequencies and different angles, which leads to a sharp decline in stealth effect under certain conditions. Thirdly, the problem of difficult maintenance and short life, the existing stealth coating is easy to crack, peel and other damage during use, once damaged, it will form a strong scattering source, which seriously affects the stealth effect, and the maintenance process is complex, which needs to be returned to the factory for large-area re-coating, with high maintenance cost. In addition, the existing coating material has poor environmental adaptability, and the performance decays quickly in harsh environments such as high temperature, high humidity and salt spray, and the service life is usually only 2-3 years, which cannot meet the long-term service demand of modern military aircraft. The existence of these problems urgently needs to develop a new generation of intelligent, multi-functional and high-reliability stealth coating materials. SUMMARY
[0005] In order to solve the above problems existing in the prior art, the present application provides a self-adaptive multi-spectral intelligent metamaterial coating system, which is a new concept of aircraft stealth coating material. The core technical problems to be solved by the present application include: how to realize multi-spectral collaborative stealth to deal with different detection means; how to give the coating layer intelligent sensing and self-adaptive adjustment ability to optimize the stealth effect; how to realize the lightweight of the coating layer while ensuring the stealth performance; and how to improve the service life of the coating layer and reduce the maintenance cost. By deeply integrating nanotechnology, metamaterial design and intelligent response materials, the present application creatively constructs a multifunctional coating system that can perceive threats, intelligently respond and self-repair.
[0006] An aircraft stealth coating material, comprising an intelligent sensing layer, a tunable metamaterial layer and a multi-spectral stealth layer arranged in turn from the surface of the aircraft skin; the intelligent sensing layer is composed of a composite network structure formed by graphene quantum dots and piezoelectric nanofibers, the particle size of the graphene quantum dots is 3-5 nanometers, and the diameter of the piezoelectric nanofibers is 100-200 nanometers; the tunable metamaterial layer comprises a liquid crystal elastomer matrix and shape memory alloy nanowires dispersed therein, the shape memory alloy nanowires are made of nickel-titanium alloy material, the diameter is 50-100 nanometers, and the length is 5-10 micrometers; the multi-spectral stealth layer comprises vanadium dioxide nanoparticles, a photonic crystal structure formed by self-assembly of silica microspheres and carbon nanotube aerogel dispersed in a polyurethane matrix, and the particle size of the vanadium dioxide nanoparticles is 20-50 nanometers.
[0007] Further, the thickness of the intelligent sensing layer is 50-100 nanometers, and the loading amount of the graphene quantum dots in the piezoelectric nanofiber network is 10-20 wt%; the piezoelectric nanofiber is polyvinylidene-fluoride-trifluoroethylene copolymer, and the β phase content is greater than 85%; the conductivity of the intelligent sensing layer is 100-200 S / m.
[0008] Further, the thickness of the tunable metamaterial layer is 500-800 micrometers; the liquid crystal elastomer is prepared by mixing liquid crystal monomer 4-methoxyphenyl-4-(6-acryloyloxyhexyloxy) benzoate, crosslinking agent 1,4-bis(4-(6-acryloyloxyhexyloxy)benzoyloxy)-2-methylbenzene and photoinitiator 2,2-dimethoxy-2-phenylphenylacetophenone at a mass ratio of 85:14:1, and then prepared by a two-step crosslinking method; the volume fraction of the shape memory alloy nanowire in the liquid crystal elastomer is 5-10%.
[0009] Further, the thickness of the multi-spectrum stealth layer is 200-300 micrometers; the addition amount of vanadium dioxide nanoparticles in the polyurethane matrix is 30-40 wt%, and the phase transition temperature is 35-45℃; the diameter of the silica microspheres is 200-300 nanometers, and the stacking layer number is 10-20 layers; the density of the carbon nanotube aerogel is 5-10 mg / cm³.
[0010] Further, the coating material further comprises a microencapsulated repair agent system, the capsule wall material of the microcapsule is urea-formaldehyde resin, and the capsule wall thickness is 500-1000 nanometers; the capsule core comprises an epoxy resin monomer and a curing agent, and the mass ratio of the epoxy resin to the curing agent is 10:1; the capsule core diameter of the microcapsule is 10-50 micrometers, and the addition amount in each functional layer is 5-10 wt%.
[0011] Further, when an electric field of 0-100 V / cm is applied to the tunable metamaterial layer, the dielectric constant is continuously adjustable in the range of 2.5-12, and the magnetic permeability is continuously adjustable in the range of 0.8-1.5; within the temperature range of 25-80℃, the shape memory alloy nanowire undergoes reversible phase transition, causing changes in the microstructure of the material.
[0012] Further, the coating material is integrated with an intelligent control unit, which includes a microprocessor with an ARM Cortex-M0 core, a sensor array distributed in the form of a 100×100 matrix, and an actuator network composed of conductive silver nanowires; the line width of the conductive silver nanowires is 10-20 micrometers; the sensor array includes electromagnetic wave detectors, temperature sensors and strain sensors.
[0013] The preparation method of the above-mentioned stealth coating material for aircraft includes the following steps: pre-treatment of aircraft skin by plasma cleaning and chemical etching to form a microstructure with a surface roughness Ra of 0.8-1.2 micrometers; preparation of a smart sensing layer by electrospinning technology, with a spinning voltage of 15-20 kV, a spinning speed of 0.5-1.0 mL / h, and a receiving distance of 15-20 cm, while simultaneously spraying graphene quantum dot dispersion and annealing at 150℃ for 2 hours; preparation of a tunable metamaterial layer by a two-step crosslinking method, in which the first step involves self-assembly of shape memory alloy nanowires under a 0.5 Tesla magnetic field with an ultraviolet light irradiation intensity of 10 mW / cm² for 30 seconds, followed by complete curing under a 60-second ultraviolet light irradiation; and preparation of a multispectral stealth layer by co-deposition technology, in which vanadium dioxide nanoparticle dispersion, silica microsphere suspension, and carbon nanotube aerogel precursor are deposited sequentially, and each layer is dried at 25±2℃ and 45±5% relative humidity after deposition.
[0014] The technical solution of this invention adopts a three-layer functional composite structure design, with each layer undertaking a specific function and working collaboratively. The intelligent sensing layer, acting as the "neural network" of the entire system, achieves real-time sensing and identification of external electromagnetic wave signals through a composite network structure of graphene quantum dots and piezoelectric nanofibers. When electromagnetic waves irradiate the coating surface, the graphene quantum dots can sensitively respond to changes in the electromagnetic field, generating corresponding electrical signals, while the piezoelectric nanofibers can sense mechanical vibrations and stress changes. The combination of these two layers enables comprehensive acquisition of key information such as the frequency, intensity, and incident angle of threat signals. The tunable metamaterial layer is the core of achieving adaptive stealth. Through the synergistic effect of liquid crystal elastomers and shape memory alloy nanowires, the microstructure of the material can undergo reversible changes under the control of an applied electric or temperature field, thereby dynamically adjusting its electromagnetic parameters. This adjustment mechanism allows the coating to optimize its absorption characteristics for different detection signals, achieving a "tailor-made" stealth effect. The multispectral stealth layer achieves comprehensive stealth across multiple wavelengths by integrating various functional materials, including vanadium dioxide nanoparticles for infrared stealth, photonic crystal structures for visible light stealth, and carbon nanotube aerogels for radar wave absorption.
[0015] This invention also innovatively introduces a self-healing function and an intelligent control system. By embedding microencapsulated repair agents into the coating, when minor damage such as microcracks occurs, the repair agents can be automatically released for in-situ repair, significantly extending the coating's service life. The intelligent control system, through an integrated microprocessor, sensor array, and actuator network, can analyze threat signal characteristics in real time, quickly calculate the optimal response strategy, and precisely control the working state of each functional layer, achieving true intelligent stealth. The entire coating system is manufactured using a gradient functionalized layer-by-layer assembly technology, ensuring good bonding and functional synergy between layers.
[0016] Compared with the prior art, the present application has significant technical advantages and innovation. In terms of stealth performance, the present application realizes radar wave absorption in the ultra-wide frequency band of 0.1-40GHz, and the radar scattering cross section can be reduced by 25-30dB; the infrared radiation characteristic is reduced by more than 80%; the visible light reflectivity can be dynamically adjusted in the range of 5%-95%, and truly realizes multi-spectral collaborative stealth. In terms of material properties, the areal density of the entire coating system is only 1.2-1.5kg / m², which is more than 60% lighter than the traditional stealth coating, and has little effect on the performance of the aircraft. In terms of intelligent level, the coating can respond to threat signal changes within 100 milliseconds, automatically optimize the stealth strategy, and improve the stealth effect by more than 40%. In terms of reliability, the self-repairing function prolongs the service life of the coating to more than 10 years, which is 3-5 times that of the traditional coating, and the maintenance cost is reduced by 70%. The present application not only solves the technical bottleneck of the existing stealth coating materials, but also opens up a new direction for intelligent adaptive stealth, providing key material technology support for the development of the next generation of stealth aircraft, and has important military application value and broad market prospects. BRIEF DESCRIPTION OF DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or the prior art description. Obviously, the drawings in the following description only illustrate the present application, and for those skilled in the art, other drawings can also be obtained without creative labor on the basis of these drawings.
[0018] Figure 1 It is a schematic diagram of the overall structure of the stealth coating material of the present application, which shows the three-layer composite structure of the coating; Figure 2 It is a schematic diagram of the microstructure of the intelligent sensing layer of the present application, which details the distribution state of the piezoelectric nanofiber network and the graphene quantum dot; Figure 3 It is a working principle diagram of the tunable metamaterial layer of the present application, which compares and shows the arrangement changes of the liquid crystal molecules and the shape memory alloy nanowires in the unactivated and activated states, as well as the corresponding electromagnetic parameter changes and radar wave absorption characteristic curves; Figure 4 It is a schematic diagram of the preparation process of the present application, which systematically shows the complete process from surface pretreatment to preparation of each functional layer; Figure 5 、 Figure 6 and Figure 7 It is a performance test comparison diagram of the present application, which comprehensively compares the differences between the new coating and the traditional coating in terms of radar scattering cross section, infrared radiation, weight and comprehensive performance through various chart forms. DETAILED DESCRIPTION
[0019] The application will be described in greater detail in connection with the accompanying drawings and specific embodiments. It is noted that the embodiments are described herein in more detail for the purpose of making the embodiments more thorough, and that other alternatives can be used by those skilled in the art without departing from the scope of the application. Also, the drawings are not necessarily drawn to scale and are merely intended for use in the description of the embodiments.
[0020] It is noted that the use of "one embodiment," "an embodiment," "certain embodiments," "certain embodiments," "some embodiments," and the like, are not to be construed as limiting the application to the particular embodiment or embodiments described, but rather to include the other embodiments that are equivalent in scope to the recited embodiment(s). Additionally, the use of the term "based on" is intended to be a shorthand for "based at least in part on."
[0021] In general, the terminology used can be understood at least in part from an analysis of the context in which the term is used. For example, the term "one or more" as used herein, depending at least in part upon the context in which the term is used, can be used to describe any feature, structure, or characteristic in a singular sense or can be used to describe combinations of features, structures, or characteristics in a plural sense. Similarly, the term "based on" as used herein, depending at least in part upon the context in which the term is used, can be understood to mean "based, at least in part, on" or "based at least in part on," and is not to be interpreted in an exclusive or exhaustive sense.
[0022] Referring to Figures 1 to 7 shown The adaptive multi-spectrum intelligent metamaterial coating system provided by the application is an innovative stealth coating material for aircraft, which combines nanotechnology, metamaterial design and intelligent response materials to form an intelligent coating system with a multi-layer composite structure. I will explain the specific implementation of this invention to you in detail, and help you understand the implementation process of each technical link.
[0023] The overall structure of the coating system includes three functional layers, from the surface of the aircraft skin to the outside in turn, intelligent sensing layer, tunable metamaterial layer and multispectral stealth layer, the thickness of each layer is controlled in the range of 50-100 nanometers, 500-800 microns and 200-300 microns respectively. The entire coating system is prepared by gradient functionalization layer-by-layer assembly technology, ensuring excellent interface bonding performance and functional synergy between layers. During preparation, the aircraft skin surface needs to be pretreated first, using plasma cleaning technology to remove surface organic contaminants, then forming a micro-nano scale rough structure on the surface of aluminum alloy or composite material through chemical etching, which can significantly improve the adhesion of the subsequent coating. After pretreatment, the skin is placed in a clean room environment with a temperature controlled at 25±2℃ and a relative humidity controlled at 45±5% for coating preparation.
[0024] The preparation of the intelligent sensing layer uses in-situ growth technology. First, prepare the graphene quantum dot dispersion, disperse the graphene quantum dots with a particle size of 3-5 nanometers in N-methyl pyrrolidone solvent, the concentration is controlled at 0.5-1.0 mg / mL, and the dispersion is uniform by ultrasonic treatment for 30 minutes. At the same time, prepare the piezoelectric nanofiber precursor solution, dissolve polyvinylidene fluoride-trifluoroethylene copolymer in a mixed solvent of dimethylformamide and acetone, the polymer concentration is 15-20 wt%, and the solvent ratio is 7:3. Through electrospinning technology, under a high voltage electric field of 15-20 kilovolts, the precursor solution is spun into piezoelectric nanofibers with a diameter of 100-200 nanometers, and the graphene quantum dot dispersion is sprayed at the same time to make the quantum dots uniformly embedded in the fiber network. This process needs to accurately control the spinning speed to be 0.5-1.0 mL / h, the receiving distance to be 15-20 centimeters, the environmental temperature to be maintained at 25±2℃, and the relative humidity to be less than 40%. The prepared sensing layer is annealed at 150℃ for 2 hours to make the β phase content of the piezoelectric nanofiber reach more than 85%, so as to obtain excellent piezoelectric performance.
[0025] The preparation of the tunable metamaterial layer is a key technical link of the whole system, which needs to precisely three-dimensionally structure and assemble the liquid crystal elastomer and shape memory alloy nanowires. The synthesis of the liquid crystal elastomer adopts a two-step crosslinking method. First, the liquid crystal monomer 4-methoxyphenyl-4-(6-acryloyloxyhexyloxy) benzoate, the crosslinking agent 1,4-bis(4-(6-acryloyloxyhexyloxy)benzoyloxy)-2-methylbenzene and the photoinitiator 2,2-dimethoxy-2-phenylacetophenone are mixed uniformly in a mass ratio of 85:14:1, and the first step of crosslinking is carried out by ultraviolet light irradiation under nitrogen protection. The light intensity is 10 mW / cm2, and the time is 30 seconds, forming a weak crosslinked network with a liquid crystal phase. Then, the shape memory alloy nanowire dispersion liquid is added dropwise to the surface of the liquid crystal elastomer. The nanowires are made of nickel-titanium alloy material, with a diameter of 50-100 nanometers and a length of 5-10 micrometers, and a dispersion concentration of 5-10 mg / mL. Through the magnetic field assisted self-assembly technology, the nanowires form an ordered arrangement in the liquid crystal elastomer under the action of a magnetic field of 0.5 tesla, and the arrangement direction is consistent with the orientation direction of the liquid crystal molecules. Finally, the second step of crosslinking is carried out, and the liquid crystal elastomer network is completely cured by ultraviolet light irradiation for 60 seconds, and the shape memory alloy nanowires are locked in the three-dimensional ordered structure. This composite structure can realize continuous tuning of the dielectric constant in the range of 2.5-12 and the magnetic permeability in the range of 0.8-1.5 when an electric field of 0-100 V / cm or a temperature change of 25-80℃ is applied.
[0026] The multispectral stealth layer is prepared by using a multi-component co-deposition technology to simultaneously deposit vanadium oxide nanoparticles, photonic crystal microspheres and carbon nanotube aerogel precursors to form a functional composite coating. The vanadium oxide adopts vanadium dioxide material, and monodisperse nanoparticles with a particle size of 20-50 nanometers are prepared by a hydrothermal method, and the phase transition temperature is controlled in the range of 35-45℃, so that it can work effectively under normal flight environment. The vanadium dioxide nanoparticles are dispersed in a polyurethane matrix, and the addition amount is 30-40wt%, and the dispersion is uniformly ensured by ball milling for 8 hours. The photonic crystal structure is formed by self-assembly of silica microspheres, and the microsphere diameter is accurately designed according to the target stealth wavelength. For visible light stealth, the microsphere diameter is selected to be 200-300 nanometers, and a face-centered cubic close-packed structure is formed on the surface of the substrate by a vertical deposition method, and the number of stacked layers is controlled to be 10-20 layers. The carbon nanotube aerogel is grown in situ by chemical vapor deposition method, using ferrocene as catalyst precursor and ethylene as carbon source, and grown at a reaction temperature of 750℃ for 30 minutes to form an ultra-light porous structure with a density of only 5-10 mg / cm3. The three kinds of functional materials are integrated by layer-by-layer assembly, and the thickness of each material layer is controlled to be 50-80 micrometers, 80-120 micrometers and 70-100 micrometers respectively.
[0027] To realize the self-repairing function, a microencapsulated repairing agent system needs to be added during the coating preparation process. The microcapsules use urea-formaldehyde resin as the capsule wall material, the capsule core contains epoxy resin monomer and curing agent, the capsule wall thickness is 500-1000 nanometers, and the capsule core diameter is 10-50 microns. The microcapsules are prepared by in-situ polymerization method, epoxy resin E-51 and curing agent diethylenetriamine are mixed in a mass ratio of 10:1 as the capsule core material, and the capsule wall is formed by the polycondensation reaction of urea-formaldehyde prepolymer at the oil-water interface. The prepared microcapsules are uniformly dispersed in each functional layer of the coating at an addition amount of 5-10wt%, when the coating appears microcracks, the stress concentration at the crack tip will make the microcapsules break, release the repairing agent to fill the cracks, and complete the curing repair within 24 hours at room temperature, the repair efficiency can reach more than 85%.
[0028] The integration of the entire coating system requires the configuration of an intelligent control unit, which integrates microprocessors, sensor arrays and actuator networks inside the coating using flexible printed circuit technology. The microprocessor uses an ultra-low power ARM Cortex-M0 core with a working frequency of 48MHz and a power consumption of less than 1 milliwatt. The sensor array includes electromagnetic wave detectors, temperature sensors and strain sensors, which are distributed in a 100x100 matrix on the surface of the coating with a spatial resolution of centimeters. The actuator network is constructed by conductive silver nanowires with a line width of 10-20 microns, which can independently apply control signals to each region of the tunable metamaterial layer with a response time of less than 100 milliseconds. The control algorithm uses an adaptive optimization strategy to quickly determine the optimal material parameter configuration based on the real-time detected threat signal characteristics through a lookup table method, and then accurately adjusts the working state of each layer through closed-loop feedback control.
[0029] EMBODIMENT
[0030] In order to better illustrate the technical effects of the present application, the preparation process and performance of the stealth coating material are demonstrated through specific examples below.
[0031] Example 1: Stealth coating application for small unmanned aerial vehicles
[0032] A small unmanned aerial vehicle with a wingspan of 2 meters is selected as the test platform, and the body material is carbon fiber composite. First, the surface of the body is pretreated, argon plasma cleaning for 10 minutes, power setting 200 watts, then etching with 5% phosphoric acid solution for 3 minutes, forming a microstructure with a surface roughness Ra of 0.8-1.2 microns. In a clean room environment, an intelligent sensing layer is prepared using electrospinning technology, with a spinning time of 2 hours, obtaining a uniform fiber network layer with a thickness of 80 nanometers, and the loading amount of graphene quantum dots is 15wt%. Subsequently, a liquid crystal elastomer precursor solution is applied by spin coating, the spin coating speed is 500 revolutions / minute, the time is 30 seconds, and after two-step ultraviolet crosslinking, a tunable metamaterial layer with a thickness of 650 microns is formed, and the volume fraction of shape memory alloy nanowires is 8%. Finally, a multi-spectrum stealth layer is applied by spraying technology, the spraying pressure is 0.3 MPa, the spraying distance is 20 centimeters, and the reciprocating spraying is 6 times, with an interval of 10 minutes each time, and finally a total thickness of 250 microns of the composite coating is obtained. After testing, the coating makes the unmanned aerial vehicle radar scattering cross section in X band (8-12 GHz) reduced by 28 dB, the radiation characteristics in 3-5 microns and 8-12 microns infrared wave band are reduced by 75% and 82% respectively, the visible light reflectivity can be adjusted in the range of 8%-90%, the coating area density is 1.2 kg / m², and the weight reduction is 65% compared with the traditional stealth coating.
[0033] Example 2: Stealth coating application for fighter aircraft components
[0034] The stealth coating experiment was carried out on the inlet part of a fighter aircraft, and the base material was titanium alloy. The surface pretreatment adopted anodic oxidation process, and a 20V direct current voltage was applied in sulfuric acid electrolyte for 15 minutes to form a porous oxide layer with a thickness of 5-8 microns. The intelligent sensing layer was directly grown on the oxide layer by chemical vapor deposition method, with a deposition temperature of 200℃ and a time of 4 hours, to obtain a graphene quantum dot / piezoelectric nanofiber composite layer with a thickness of 95 nanometers and an electrical conductivity of 150S / m. The tunable metamaterial layer was manufactured by 3D printing assisted manufacturing, using improved fused deposition technology, with a printing head temperature of 180℃, a layer thickness of 100 microns, and a printing speed of 20mm / s. An 800-micron-thick metamaterial structure was obtained by 8 layers of printing, and the shape memory alloy nanowires were embedded during the printing process to realize a complex three-dimensional periodic structure. The multi-spectral stealth layer was prepared by combining magnetron sputtering and chemical vapor deposition, first sputtering a 50-nanometer-thick vanadium dioxide film as a seed layer, and then growing photonic crystal and carbon nanotube structures on it, with a total thickness of 280 microns. The average radar wave absorption rate of the coating system in the S band (2-4GHz), C band (4-8GHz) and X band is 95%, 97% and 98% respectively, the infrared emissivity can be dynamically adjusted in the range of 0.2-0.9, and the response time is less than 80 milliseconds. After 500 hours of accelerated aging test, the performance attenuation of the coating is less than 5%, and the expected service life is more than 10 years.
[0035] Example 3: Stealth modification of large transport aircraft
[0036] A large transport aircraft is modified for overall stealth coating, and the surface area of the aircraft body is about 800 square meters. Considering the special requirements of large-area construction, an automatic spraying robot system is used for coating operation. In the pretreatment stage, a laser cleaning technology is used, the laser power is 1000 watts, the scanning speed is 5 meters / minute, and the cleaning efficiency reaches 20 square meters / hour. The intelligent sensing layer is prepared by using a roll-to-roll printing technology, the pre-prepared graphene quantum dot / piezoelectric nanofiber film is attached to the surface of the aircraft body by hot pressing, the attachment temperature is 120 DEG C, the pressure is 0.5 MPa, and the attachment speed is 2 meters / minute. The tunable metamaterial layer adopts a modular design, and the standardized metamaterial units are prepared in advance, each unit has a size of 50*50 cm, a thickness of 700 microns, and is formed into an overall coating by conductive adhesive, and the gap between the units is filled with conductive sealant. The multi-spectrum stealth layer adopts a large-area spraying equipment, the spraying gun caliber is 8 mm, and the electrostatic auxiliary spraying technology is used to improve the coating utilization rate to more than 85%. After the overall coating is completed, the radar detection distance at the typical combat height is shortened by 60%, the infrared detection distance is shortened by 55%, and the visible light camouflage effect makes the aircraft contour blurring degree increased by 3 times. The overall coating weight is only 450 kg, which is reduced by 1350 kg compared with the traditional stealth coating, and has little effect on the performance of the aircraft. At the same time, the coating has a self-diagnosis function, can monitor the coating state in real time, and automatically alarms when the local damage area exceeds 10 square centimeters, and the maintenance personnel can complete the on-site repair within 30 minutes through the portable repair equipment.
[0037] As can be seen from these embodiments, the aviation aircraft stealth coating material provided by the application has excellent multi-spectrum stealth performance, ultra-lightweight characteristics and intelligent adaptive ability, can meet the stealth requirements of different types of aircraft, and has a wide application prospect.
[0038] The present application encompasses any substitutions, modifications, equivalent methods and schemes made on the essence and scope of the present application. In order for the public to have a thorough understanding of the present application, specific details are described in the following preferred embodiments of the present application, and the present application can also be completely understood without the description of these details to those skilled in the art. In addition, in order to avoid unnecessary confusion to the essence of the present application, well-known methods, processes, procedures, elements and circuits are not described in detail.
[0039] The above is only the preferred embodiment of the present application, and it should be pointed out that for ordinary skilled in the art, without departing from the principle of the present application, a number of improvements and refinements can also be made, which should be considered as the protection scope of the present application.
Claims
1. An aircraft stealth coating material, characterized by: The coating material comprises, from the outside of the aircraft skin surface, an intelligent sensing layer, a tunable metamaterial layer and a multi-spectrum stealth layer; the intelligent sensing layer is composed of a composite network structure formed by graphene quantum dots and piezoelectric nanofibers, the particle size of the graphene quantum dots is 3-5 nanometers, and the diameter of the piezoelectric nanofibers is 100-200 nanometers; the tunable metamaterial layer comprises a liquid crystal elastomer matrix and shape memory alloy nanowires dispersed therein, the shape memory alloy nanowires are made of nickel-titanium alloy material, the diameter is 50-100 nanometers, and the length is 5-10 micrometers; the multi-spectrum stealth layer comprises vanadium dioxide nanoparticles, a photonic crystal structure formed by self-assembly of silica microspheres and carbon nanotube aerogel dispersed in a polyurethane matrix, and the particle size of the vanadium dioxide nanoparticles is 20-50 nanometers.
2. The aerospace aircraft stealth coating material of claim 1, wherein: The thickness of the intelligent sensing layer is 50-100 nanometers, and the loading amount of the graphene quantum dots in the piezoelectric nanofiber network is 10-20 wt%; the piezoelectric nanofiber is polyvinylidene fluoride-trifluoroethylene copolymer, and the β phase content is greater than 85%; the electrical conductivity of the intelligent sensing layer is 100-200 S / m.
3. The aerospace aircraft stealth coating material of claim 1, wherein: The thickness of the tunable metamaterial layer is 500-800 micrometers; the liquid crystal elastomer is prepared by mixing liquid crystal monomer 4-methoxyphenyl-4-(6-acryloyloxyhexyloxy) benzoate, crosslinking agent 1,4-bis(4-(6-acryloyloxyhexyloxy)benzoyloxy)-2-methylbenzene and photoinitiator 2,2-dimethoxy-2-phenylphenylacetophenone at a mass ratio of 85:14:1, and then by two-step crosslinking method; the volume fraction of the shape memory alloy nanowires in the liquid crystal elastomer is 5-10%.
4. The aerospace aircraft stealth coating material of claim 1, wherein: The thickness of the multi-spectrum stealth layer is 200-300 micrometers; the addition amount of the vanadium dioxide nanoparticles in the polyurethane matrix is 30-40 wt%, and the phase transition temperature is 35-45℃; the diameter of the silica microspheres is 200-300 nanometers, and the number of stacked layers is 10-20 layers; the density of the carbon nanotube aerogel is 5-10 mg / cm³.
5. The aerospace aircraft stealth coating material according to any one of claims 1 to 4, characterized in that: The coating material further comprises a microencapsulated repair agent system, the capsule wall material of the microcapsule is urea-formaldehyde resin, and the capsule wall thickness is 500-1000 nanometers; the capsule core comprises an epoxy resin monomer and a curing agent, and the mass ratio of the epoxy resin to the curing agent is 10:1; the capsule core diameter of the microcapsule is 10-50 micrometers, and the addition amount in each functional layer is 5-10 wt%.
6. The aerospace aircraft stealth coating material of claim 3, wherein: The tunable metamaterial layer is continuously adjustable in the dielectric constant in the range of 2.5-12 and the magnetic permeability in the range of 0.8-1.5 when an electric field of 0-100 V / cm is applied; within the temperature range of 25-80℃, the shape memory alloy nanowires undergo reversible phase transition, causing changes in the microstructure of the material.
7. The aerospace aircraft stealth coating material of claim 1, wherein: The coating material is integrated with an intelligent control unit, including a microprocessor with an ARM Cortex-M0 core, a sensor array distributed in a 100*100 matrix form, and an actuator network composed of conductive silver nanowires; the conductive silver nanowires have a line width of 10-20 microns; the sensor array includes electromagnetic wave detectors, temperature sensors, and strain sensors.
8. A process for the preparation of a stealth coating material for an aircraft as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: The aircraft skin is subjected to plasma cleaning and chemical etching pretreatment to form a microstructure with a surface roughness Ra of 0.8-1.2 microns; an intelligent sensing layer is prepared by electrospinning technology, with a spinning voltage of 15-20 kV, a spinning speed of 0.5-1.0 mL / h, and a receiving distance of 15-20 cm, while spraying a graphene quantum dot dispersion liquid, and annealing at 150°C for 2 hours; a tunable metamaterial layer is prepared by a two-step crosslinking method, with a first step of ultraviolet light irradiation at an intensity of 10 mW / cm² for 30 seconds, and a second step of ultraviolet light irradiation for 60 seconds for complete curing; a multi-spectrum stealth layer is prepared by co-deposition technology, with vanadium dioxide nanoparticle dispersion liquid, silica microsphere suspension, and carbon nanotube aerogel precursor being sequentially deposited, and each layer being dried at 25±2°C and a relative humidity of 45±5% after deposition.
